2012
DOI: 10.1097/ijg.0b013e318220daf0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Corneal Biomechanical Properties in Normal Tension Glaucoma and Comparison With Open-angle Glaucoma, Ocular Hypertension, and Normal Eyes

Abstract: NTG was associated with significantly lower CRF than chronic POAG and N patients. CH and CRF could be a useful tool in early diagnosis of NTG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 19 publications
1
40
0
1
Order By: Relevance
“…[1][2][3][12][13][14][15][16][17][18][19][20][21][22] Central corneal thickness (CCT) has received the most attention in this regard, spurred by findings from the Ocular Hypertension Treatment Study (OHTS) in which CCT was the strongest independent predictor of conversion from ocular hypertension (OH) to primary open-angle glaucoma (POAG). 22 Furthermore, the OHTS investigators reported that after subjects were split into thin, intermediate, and thick CCT subgroups, subjects in the thinnest CCT subgroup were more than three times as likely to develop glaucoma compared with subjects in the thicker CCT subgroup.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][12][13][14][15][16][17][18][19][20][21][22] Central corneal thickness (CCT) has received the most attention in this regard, spurred by findings from the Ocular Hypertension Treatment Study (OHTS) in which CCT was the strongest independent predictor of conversion from ocular hypertension (OH) to primary open-angle glaucoma (POAG). 22 Furthermore, the OHTS investigators reported that after subjects were split into thin, intermediate, and thick CCT subgroups, subjects in the thinnest CCT subgroup were more than three times as likely to develop glaucoma compared with subjects in the thicker CCT subgroup.…”
Section: Introductionmentioning
confidence: 99%
“…4 The ORA provides the corneal hysteresis (CH) and the corneal resistance factor, which are considered to reflect the corneal biomechanical properties. 2 Studies have shown significant differences between the CH and corneal resistance factor values in normal eyes and those in eyes with glaucoma, [5][6][7] keratoconus, 4 high myopia, 8,9 and acquired pit of the optic nerve head 10 and eyes that have undergone refractive surgery. 11 Although these studies have suggested the relevance of corneal biomechanics in ocular clinical practice, studies also have reported the limitations of CH and corneal resistance factor as diagnostic tools.…”
mentioning
confidence: 99%
“…The ORA-based corneal biomechanical parameters, although significantly lower in glaucoma eyes (including PACG) compared to normals, [4][5][6]8 do not appear to be related to disease severity within PACG subjects. Our findings of the significant associations between CH and CRF with CCT are comparable with the findings in eyes with POAG.…”
Section: Discussionmentioning
confidence: 99%
“…3 Several studies have reported that CH is lower in eyes with glaucoma compared to normals. [4][5][6] Within the open angle subtypes, CH is reported to be lower in primary open angle glaucoma (POAG) compared to those with ocular hypertension (OHT) or glaucoma suspect. [5][6][7] However, within POAG itself, reports about CH differences between normal tension glaucoma (NTG) and high-tension glaucoma (HTG) have been variable.…”
mentioning
confidence: 99%
See 1 more Smart Citation